Island lives : historical archaeologies of the Caribbean - Farnsworth, Paul 1958- (University of Alabama, 2001)
Long before the founding of Jamestown in 1607, there were Spanish foros, bustling towns, sugar plantations, and sea trade flourishing in the Caribbean. Whereas richer nations, particularly the United States, may viewthe Caribbean today as merely a place for sun and fun, the island colonies were at one time far more important and lucrative to their European empire countries, as competing colonial powers vied with each other for military and economic advantage in the Western Hemisphere, events in the Caribbean directly influenced the American mainland. This is one rationale for the close study of historical archaeology in the Caribbean. Another is the growing recognition of how archaeological research can support the definingof national identities for the islands, many of them young independent states struggling to establish themselves economically and politi cally. By looking at cases in the French West Indies, specifically on Guadeloupe, in the Dutch Antilles, and Aruba, in the British Bahamas, on Montserrat and St. Eustatius, on Barbados, and within the U.S Virgin Islands, the contributors to Island Lives have produced a broad overviewof Caribbean historical archaeology.